Penegakan Hukum Terhadap Pelaku Tindak Pidana Judi Online Ditinjau Dari Ilmu Kriminologi - Hidayat, Afwa Hilman; Apriani, Rani (Peneliti.net, 2024)
The development of information technology in the current era of globalization has made it easier for everyone to obtain useful information. However, technological advances in the field of information can lead to crimes in new forms, such as gambling by using online media as a means of carrying out online gambling actions. This phenomenon is one of the most serious social problems because it has a negative impact on national interests, especially for the younger generation who should be the next generation of the nation to build this country into a developed and developing country. The purpose of this study is to find out law enforcement and countermeasures against online gambling actions and to find out what are the factors that influence the occurrence of online gambling. Therefore, the method used in this study uses qualitative methods gambling. This study produces the existence of factors that require the occurrence of online gambling crimes and explains about law enforcement efforts against online gambling.